MACHINE LEARNING IN HEALTHCARE: AN OVERVIEW - Arpad KEREST ELY; Lucian Mircea SASU; Marius Sabin TĂBÎRCĂ (Bulletin of the Transilvania University of Brasov, 2018)
Machine learning has been widely used in many domains lately and an increasing trend can be observed. New algorithms have been developed and older ones have been improved or combined to get better results. Healthcare is one of the domains that has seen the bene ts of using these new computation methods. Considering that early prototypes of arti cially intelligent doctors already exist [2], in the not too distant future we could be greeted by robot nurses or even doctors at medical facilities. This paper aims to present, analyze and discuss some of the latest advancements in machine learning from the healthcare point of view. Important aspects that this paper covers are: recently used machine learning algorithms in healthcare, data available for research purpose and the elds that healthcare extends to. A conclusion based on these aspects is drawn, whether there is a need and possibility for potential further development of machine learning algorithms in healthcare
Keywords: machine learning; healthcare